Correction to: Development and evaluation of a patient passport to promote self-management in patients with heart diseases - Sabine Stamm-Balderjahn; Rebecca Falinski; Susanne Rossek; Karla Spyra (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.